Supplementation of (Trigonella foenum-graecum L.) Fenugreek Leaves Stimulates the Insulin Action in Streptozotocin- Induced Diabetic Rats - Menon2, Annida Balakrishnan1* and Venugopal. P. (Journal of Ecobiotechnology, 2010)
<span style="font-size: 10pt; line-height: 110%; font-family: ";Garamond";,";serif";; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">Trigonella foenum-graecum<span style="font-size: 10pt; line-height: 110%; font-family: ";Garamond";,";serif";; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;"> (Fenugreek) leaves exhibit antidiabetic and antioxidant properties. The present study was designed to elucidate the insulin stimulatory effect on supplementation of fenugreek leaves in streptozotocin-induced diabetes in rats. Supplementation of fenugreek leaves mixed with diet at doses of 0.5g and 1.0g/kg of body weight twice daily to diabetic rats for a period of 45days resulted in change in bodyweight, increase in weight of pancreas, enhances the insulin levels and a significant decrease in fasting blood glucose levels. Histopathological observations showed marked changes of the pancreas in treatment with the fenugreek leaves improved the functional state of the pancreatic Î²-cells and partially retained the damage caused by streptozotocin to the pancreatic islets. These findings of our study clearly indicate the insulin stimulatory effect of fenugreek leaves. The effect observed with the fenugreek leaves was better than that of glibenclamide (600 Âµg/kg bodyweight). <span style="font-size: 10pt; line-height: 110%; font-family: ";Garamond";,";serif";; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">---------------------------------------------------------------------------------- <span style="font-size: 10pt; line-height: 110%; font-family: ";Garamond";,";serif";; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;"> 1Reader, Department of Biochemistry, Sathyabama University Dental College and Hospital, Chennai, Tamil Nadu, India 2Director of Research, Ex-Dean of Science, Department of Biochemistry and Biotechnology, Annamalai University, Chidambaram *Corresponding author, Email: annidabalakrishnan@yahoo.co.in, Ph: +91-44- 24503064, Mob: +91-9244488676 Cite This Article As: Annida Balakrishnan and Venugopal. P. Menon. 2010. Supplementation of (Trigonella foenum-graecum L.) Fenugreek Leaves Stimulates the Insulin Action in Streptozotocin- Induced Diabetic Rats. J. Ecobiotechnol. 2(3): 26-32.